Martian high‐altitude photoelectrons independent of solar zenith angle. Issue 4 (30th April 2016) - Xu, Shaosui; Liemohn, Michael; Bougher, Stephen; Mitchell, David
Abstract: Many aspects of the Martian upper atmosphere are known to vary with solar zenith angle (SZA). One would assume that dayside photoelectron fluxes are also SZA dependent, especially when transport along a semivertical magnetic field line is significant. However, our investigation presented here of the observed Martian high‐altitude (∼400 km) photoelectron fluxes by the magnetometer/electron reflectometer (MAG/ER) instruments on board Mars Global Surveyor (MGS) shows that the photoelectron fluxes are better correlated with just the solar irradiance, without SZA factored in, and also that the median photoelectron fluxes are independent of SZA, especially for high energies (above 100 eV). For lower energies (below 70 eV), the observed fluxes tend to vary to some degree with SZA. Such counterintuitive results are due to the existence of a photoelectron exobase, only above which the photoelectrons are able to transport and escape to high altitudes. Two methods are used here to determine the altitude range of this exobase, which varies between 145 km and 165 km depending on the atmosphere and SZA. Through our SuperThermal Electron Transport (STET) model, we found that the integral of the production rate above the photoelectron exobase, and therefore the high‐altitude photoelectron fluxes, is rather independent of SZA. Such an independent relationship concerns energy redistribution in the Martian upper atmosphere, using photoelectrons to map magnetic topology and connectivity, as well as ion escape. This finding can also be carefully adapted to other solar bodies with semivertical magnetic fields at ionospheric altitudes, such as Earth, Jupiter, and Saturn. Key Points: High‐altitude photoelectron fluxes are independent of SZA for energies above a few tens of eV SZA partially controls the low‐energy photoelectron fluxes Our simulations show that the photoelectron exobase is around 145–165 km